Collapse of the world's largest herbivores - Ripple, William J.; Newsome, Thomas M.; Wolf, Christopher; Dirzo, Rodolfo; Everatt, Kristoffer T.; Galetti, Mauro [UNESP]; Hayward, Matt W.; Kerley, Graham I.H.; Levi, Taal; Lindsey, Peter A.; Macdonald, David W.; Malhi, Yadvinder; et al. (American Association for the Advancement of Science (AAAS), 2015)
Large wild herbivores are crucial to ecosystems and human societies. We highlight the 74 largest terrestrial herbivore species on Earth (body mass≥ 100 kg), the threats they face, their important and often overlooked ecosystem effects, and the conservation efforts needed to save them and their predators from extinction. Large herbivores are generally facing dramatic population declines and range contractions, such that ∼60% are threatened with extinction. Nearly all threatened species are in developing countries, where major threats include hunting, land-use change, and resource depression by livestock. Loss of large herbivores can have cascading effects on other species including large carnivores, scavengers, mesoherbivores, small mammals, and ecological processes involving vegetation, hydrology, nutrient cycling, and fire regimes. The rate of large herbivore decline suggests that ever-larger swaths of the world will soon lack many of the vital ecological services these animals provide, resulting in enormous ecological and social costs.